Integrated transcriptomics and metabolomics reveal the molecular characteristics and metabolic regulatory mechanisms among different muscles in Minxian black fur sheep - Huihui Wang; Zilong Liu; Hai Yang; Yaqin Bai; Qiao Li; Xingcai Qi; Dengpan Li; Xingxu Zhao; Youji Ma (BMC Genomics)
Abstract Background Mammalian skeletal muscle is comprised of heterogeneous fibers with various contractile and metabolic properties that affect muscle flavor. Thus, it is of great significance to identify and characterize the potential molecular characteristics and metabolic regulatory mechanisms associated with muscle fiber properties. Results In this study, the muscle samples (Biceps femoris; longissimus dorsi; and infraspinatus) from Minxian black fur sheep were used to perform transcriptome and metabolome analyses. Then, the key genes regulating the metabolism of important flavor precursors (amino acids and lipids) were explored by integrating transcriptome and metabolome. Consequently, we identified 432 differentially expressed genes, which were mainly involved in muscle development and function maintenance (e.g., myofibril, myocyte differentiation, etc.), metabolism (e.g., fatty acid metabolism, arachidonic acid metabolism, PPAR signaling pathway, and PI3K-Akt signaling pathway, etc.), and homeostasis (e.g., regulation of actin cytoskeleton, ECM-receptor interaction, calcium signaling pathway, etc.). A total of 58 key genes affecting muscle fiber properties, including MYL2, HOXA/C/D, MYBPH8, MYH8, etc., were screened, which characterized the molecular differences in muscle fiber metabolic properties between oxidative and glycolytic muscle. Meanwhile, we identified 463 differentially accumulated metabolites. Except for glycerophospholipids, most flavor metabolites were higher in oxidative muscle. Subsequently, key genes highly related to flavor amino acids were identified by weighted gene co-expression network analysis, such as ALDH6A1, BCKDHB, SLC16A7, LDHB, etc. Based on KEGG enrichment analysis, a regulatory network with both lipid metabolism and its crosstalk with other metabolic pathways was constructed. Conclusions In conclusion, this study provides an in-depth understanding of the molecular mechanism of differences in muscle fiber properties among different muscles of Minxian black fur sheep, and also lays a foundation for further exploration of the regulatory mechanism of key genes on flavor metabolites.